How did wars dampen trade in the MENA region?. Issue 60 (25th December 2016) - Karam, Fida; Zaki, Chahir
ABSTRACT: The article investigates the impact of wars on trade in the Middle East and North African region. Using an augmented gravity model that controls for the endogeneity problem in our estimation, we introduce a war variable and distinguish between different types of conflicts. The results show that wars have a significantly negative impact on exports, imports and trade. Civil conflicts hinder exports, imports and trade significantly. The disaggregated version of the gravity model shows that non-state conflicts have a detrimental effect on bilateral trade flows in manufacturing, and that none of the conflicts do affect trade in services. We also find that, on average, a conflict is equivalent to a tariff of 5% of the value of trade.